Hydrogen production from catalytic steam reforming of biomass pyrolysis oil or bio-oil derivatives: A review. (17th July 2020) - Setiabudi, H.D.; Aziz, M.A.A.; Abdullah, Sureena; Teh, L.P.; Jusoh, R.
Abstract: Steam reforming of biomass pyrolysis oil or bio-oil derivatives is one of the attractive approaches for hydrogen production. The current research focused on the development of promising catalysts with favorable catalytic activity and high coke resistance. Noble metal such as Rh has been proven to achieve promising reforming reaction efficiencies. However, Ni has attracted considerable attention owing to its stability, cost effectiveness, and good activity in breaking C–C and C–H bonds. Nevertheless, Ni-based catalysts have serious carbon deposition problems arising from chemical poisoning, metal sintering, and poor metal dispersion. This paper attempted to review the current trends in catalyst development considering the aspects of supports, metals, and promoters as an effort to find possible solutions for the limitations of Ni-based catalysts. The present review also covered the current understanding on the reaction mechanisms as well as the future prospects in the field of steam reforming catalysts. Graphical abstract: Image 1 Highlights: Catalysts efficiency rely on nature of metal, support, and metal-support interface. Advanced catalyst synthesis is a new direction for achieving promising catalyst. Mechanism of oxygenates compounds steam reforming is well discussed. Further studies to elucidate mechanism of bio-oil steam reforming are required.